The Determinants of Total Factor Productivity in Polish Subregions. Panel Data Analysis; Determinanty łacznej produktywnosći czynnikoẃ produkcji w podregionach w Polsce - Barbara Danśka-Borsiak; Iwona Laskowska (Comparative Economic Research. Central and Eastern Europe, 2012)
The significant role of TFP in stimulating the long-run economic development induces researchers to seek for the sources of the TFP growth. The mail goals of the paper are: to estimate the level of TFP in the years 2003-2009 at the level of subregions, and to define the factors which determine this estimated TFP level. The first hypothesis being verified is, that the role of the quality of human capital in stimulating long-run economic growthis crucial and can be measured by the model. The second hypothesis is, that there are some factors affecting the TFP level which are common in all subregions. – – Znaczaca role TFP w stymulowaniu długookresowego rozwoju gospodarczego skłania badaczy do poszukiwania zŕod́eł jej wzrostu. Głoẃne cele badanṕrezentowanych w artykule sa nastepujace: oszacowanie wartosći TFP w latach 2003-2009 w podregionach, a nastepnie okresĺenie czynnikoẃ determinujacych łaczna produktywnosććzynnikoẃ produkcji. Z zastosowaniem modelu ekonometrycznego podjeto prob́e weryfikacji hipotezy, izj̇akosći kapitału ludzkiego odgrywa istotna role w stymulowaniu długookresowego wzrostu gospodarczego. Zgodnie z kolejna hipoteza istnieja czynniki wpływajace na poziom TFP, wspoĺne dla wszystkich podregionoẃ.
Keywords: 330